ANALISIS EKONOMI USAHA TANI ANGGOTA SIMPAN PINJAM KELOMPOK PEREMPUAN PROGAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN DI KECAMATAN SELOREJO KABUPATEN BLITAR - Niza Kenyo Ganda Arum; Arfida BR (Jurnal Ekonomi Pembangunan, 2017)
This study aimed to analyze the differences bothincomeand yieldin Farmer’s SPP group before and after receiving PNPM-MPdcredit. Primary data obtained from 50 respondents which were selected by purposive sampling.This research was conducted by qualitative research design by means descriptive.Thedata selected fromincome and yield before and after receiving PNPM-MPdcredit.While the data were processed by using a different test analysis paired sample mean.Analyzes result indicated that there was a mean differential both income and outcome production on Farmer’s SPP group before and after the PNPM-MPd received credit. Evenly, the outcome production is about 8,28 Kw before receiving the credit and it was about 10,12 Kw after receiving the credit. However, the income had indicated about Rp 3.043.000 before the PNPM-MPd received credit and the outcome had indicated about Rp 5.160.000 after receiving thecredit. From the yield,   it showed a more superior in income. This affected by cost factor through the rise.